Intraneural injection of a test dose of local anesthetic in peripheral nerves – does it induce histological changes in nerve tissue?. Issue 1 (25th October 2016) - Wiesmann, T.; Steinfeldt, T.; Exner, M.; Nimphius, W.; De Andres, J.; Wulf, H.; Schwemmer, U.
Abstract : Background & Objectives: Most anesthesiologists use the injection of a test dose of local anesthetic in order to evaluate the final needle tip position. Thus, the intraneural injection of a full dose can be avoided. The aim of this study was to analyze whether an intraneural injection of a test dose of bupivacaine could trigger histological changes. Methods: Intraneural injections under direct vision were performed in 40 brachial plexus nerves in seven anesthetized pigs. Tibial nerves served as positive and negative controls. Two milliliter of bupivacaine 0.5% was injected in three nerves on the left brachial plexus. For control of local anesthetic's toxicity Ringer's solution was applied intraneurally on the right side. After maintaining 48 h of general anesthesia, the nerves were resected. The specimens were processed for histological examination and assessed for inflammation (hematoxylin and eosin stain, CD68‐immunohistochemistry) and myelin damage (Kluver–Barrera stain). The degree of nerve injury was rated on a scale from 0 (no injury) to 4 (severe injury). Results: Statistical analysis showed no significant differences between the bupivacaine group [median (interquartile range) 1 (1–1.5)] and the Ringer's solution group [1 (0.5–2) P = 0.772]. Mild myelin alteration was found in 12.5% of all specimens following intraneural injection, irrespective of the applied substance. Conclusions: "In our experimental study, intraneural injection of 2 ml of bupivacaine or Ringer's solution showed comparable mild inflammation. Nevertheless, inflammation can only be prevented by strictly avoiding nerve perforation followed by intraneural injection, as mechanical nerve perforation is a key factor for evolving inflammation.